BUYRAKLARDA URAT TOSHLARI HOSIL BO‘LISHI VA DAVOLASH YO‘LLARI - Oʻrmonov Muhammadyusuf Islomjon oʻgʻli,; Mamazulunov Nurmuhammad, (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract:  Uric  acid  kidney  stones  are  crystals  formed  due  to  excessive accumulation of purines in the urine. They often cause pain, difficulty in urination, and sometimes  remain  asymptomatic.  This  article  explores  the  causes,  prevention strategies, and treatment options for uric acid stones in an engaging and clear manner. Maintaining a healthy lifestyle, proper diet, and medications can effectively manage this condition.